Benzene and 1, 3 Butadiene Concentration and Its Potential Health Impact in Chiang Mai, Thailand - Thongkum, Wisit; Wibuloutai, Jindawan; Thitisutthi, Sawan (European Journal of Sustainable Development, 2017)
Air pollution is contamination of the outdoor or indoor environment by any physical, biological or chemical agent that modifies the natural characteristics of the atmosphere. Air pollution can cause long-term and short-term health effects. An emerging air pollution issue in Thailand is the air toxics problem resulting from transportation and industrial activities. Cancer risk of benzene at Chiang Mai City Hall was within 3.00x10-6 – 1.20x10-6 and Yupparaj Wittayalai School was within 9.30x10-6 – 1.20x10-5 respectively. The excess lifetime cancer risk of the population was calculated as the product of the benzene level and the unit risk for benzene. The results indicated that the population was estimated to receive an excess lifetime cancer risk greater than 1.0x10-5, which is proposed as the permissible maximum value for individual excess lifetime cancer risk by the Japan Environmental Agency (JEA). As for 1, 3-butadiene, cancer risk at Chiang Mai City Hall was within 3.00x10-6 – 1.20x10-6 and at Yupparaj Wittayalai School were 9.30x10-6 – 1.20x10-6, respectively. The results indicated that the population was estimated to receive an excess lifetime cancer risk less than 1x10-5 at two stations, which is proposed as the permissible maximum value by Japan Ministry of the Environment. Keywords: Benzene, 1, 3-butadiene, Cancer risk, Health impact